Nurses' perceptions of medical procedures and nursing practices for older patients with non‐cancer long‐term illness and do‐not‐attempt‐resuscitation orders: A vignette study - Asaka Higuchi; Azusa Yoshii; Morihito Takita; Masaharu Tsubokura; Hiroki Fukahori; Rika Igarashi (Wiley, 2020)
Abstract Aim To elucidate influence of a do‐not‐attempt‐resuscitation (DNAR) order on nurses' perceptions of the medical procedures and nursing practices for non‐cancer older patients. Design A vignette‐based questionnaire study. Methods A questionnaire survey asking nurses their perceptions of clinical practices for the following three vignettes was performed in a community hospital in Japan (N = 120): the control vignettes with an older patient with repeated heart failure who was living alone and the other two with either an absence of relatives or a diagnosis of dementia. We also prepared additions to each vignette describing a DNAR order. Results Nurses' perception on cardiopulmonary resuscitation, defibrillation, blood tests and intravenous nutrition showed statistically significant and minimally important declines after the DNAR order compared with before for all three vignettes (p < .001). DNAR orders can influence nurses' perceptions of clinical practices for non‐cancer older patients with chronic heart failure.